Studies on the Clinical Syndromes of Dogs Linked with Babesia gibsoni - Kachave, Omkarsing Rajeshsing; Meshram, Milind D; Borikar, Sudhirkumar T; Khillare, Kavita P; Mote, Chandrakant. S; Mhase, Prashant P (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Among the 24 PCR positive cases of B. gibsoni in dogs, 9 (37.5%) were associated with various clinical syndromes. According to the set  criterion of various clinical syndromes 4/9 (44.44%) dogs showed hepatopathy, 2/9 (22.22%) showed acute kidney failure and pancreatitis  and 1/9 (11.11%) was presented with acute respiratory distress syndromes. Remaining 2 cases of Babesia gibsoni did not show any clinical  syndromes as per the set criateria. The mean values of serum biochemical parameters observed among 24 dogs were ALT 73.64±6.80  U/L, ALP 141.80±11.1 U/L, BUN 25.00±2.10 mg/dL, creatinine 0.90±0.08 mg/dL, amylase 639.10±49.10 U/L, and lipase 379.50±47.90  U/L. Among 9 babesiosis poisitive dogs with clinical syndromes, German Shepherds accounted for the largest number (4/9; 44.44%),  followed by non-descript and Labradors each 2/9 (22.22%) and Dobermans 1/9 (11.11%).
Keywords: :Acute renal failure; Acute respiratory distress syndrome; Babesiosis; Hepatopathy; Pancriatitis